Managing a culturally diverse workforce: A managerial accountant perspective - Hugo, Jacques; Sauerman, Roelof; Schutte, Hannorite; Schutte, Danie; Eeden, Eben Van (International Journal of Management Excellence (ISSN: 2292-1648), 2019)
The role of the Management Accountant has seen a dramatic shift in the past century as the primary function has gradually moved from a technical to a strategic role that focuses on creating a competitive advantage for the organization. This shift from “measuring” to “managing” demands that the management accountant possess a broader range of skills, specifically softer skills, that is needed for managing and leading the people of the organisation in their roles. However, the 21st century work place is much more culturally diverse in its workforce today, than it was in previous decades. This diversity of the people in the organization has the potential to create unequalled competitive advantage if managed well, or to it has the potential to sink an organization if not managed well. This study aims at exploring different models that can be used by the management accountant to be better at understanding and ultimately managing the people within the company in a way that brings the best out of the diversity of its people in working to create a sustainable competitive advantage.